Weeds Vegetation in Rubber Plantations at Different Altitudes in Indragiri Hulu District, Riau Province, Indonesia - Dinny Cahyantika; Novita Hera; Irwan Taslapratama (Jurnal Riset Perkebunan, 2025)
The rubber plantations owned by smallholders in Indragiri Hulu Regency are inseparable from management problems, especially the management of weeds. This study identifies and analyzes dominant weed types at two different heights, namely 6 m asl and 28 m asl. In this study, the parameters of the observations and calculations are important value indexes such as density, frequency, dominance, and significant values. Then, there is the diversity index or diversity index and similarity index. The method used in this study is a field survey method with different altitude levels, employing purposive sampling in rubber plantation areas in Sekip Hulu Village, Rengat District, Indragiri Hulu Regency. The results showed that based on the SDR value, the 3 most dominating weeds in rubber plantations at an altitude of 6 m asl were Asystasia gangetica, Eleusine indica and Syzygium polyanthum which each obtained SDR values of 50.05%, 12.11% and 8.01%. , while at an altitude of 28 m asl, it was dominated by Ottochloa nodosa, Clidemia hirta, and Melastoma malabathricum, which respectively obtained SDR values of 56.34%, 15.39%, and 9.97%. Based on the value of diversity or diversity value, it shows that, as the altitude increases, the number of weed species found decreases from a height of 6 masl to 28 m asl. The importance of this weed vegetation study lies in selecting the most appropriate control method, whether mechanical, chemical, or biological, in Rubber plantations.